Un texto olvidado de Rafael Dieste, escrito y publicado durante la guerra civil española - Núñez, César Andrés (El Colegio de México, 2009)
This article offers an essay by Rafael Dieste, “Sobre los esperpentos de don Ramón del Valle-Inclán”, published only once –on January 9th, 1939– in Los Lunes de El Combatiente, a weekly literary sheet from the XI Brigade of the East Army of the II Spanish Republic. Unknown until now, this text represents an interesting testimony on Dieste’s work during the last months of the Spanish Civil War. In addition, it is the last essay published by Dieste before leaving for exile, and is an important document on the cultural activities of Republican writers during this period.